More balls through Windows. (Economist, 2004)
The article discusses whether Microsoft is finally about to face real competition in desktop-computer software. For years, many in the computer business have hoped that Linux, a freely available computer operating system, would become a viable alternative to Microsoft's Windows, the near universal standard for the world's personal computers. Within the past month, some of the world's most powerful technology firms have pledged considerable support for Linux on the desktop, including Dell and Sun Microsystems. By the end of the decade, Linux's share could grow, reckons Al Gillen, an analyst at technology consultancy IDC, displacing Macs as the main alternative. That would still fall far short of Linux's growing popularity in the market for powerful server computers. Linux aficionados, however, say its chances on the desktop should be better. However, despite improvements Linux faces obstacles. Some of Linux's main backers have relatively modest ambitions for the operating system. Linux's main appeal is likely to be to companies rather than home users. But the future is uncertain, and Linux still might yet represent another kind of threat to Microsoft.